Table tennis match analysis: a review - Fuchs, M.; Liu, R.; Malagoli Lanzoni, I.; Munivrana, G.; Straub, G.; Tamaki, S.; Yoshida, K.; Zhang, H.; Lames, M. (Journal of Sports Sciences, 2018)
In table tennis, many different approaches to scientific founded match analysis have been developed since the first ones in the 1960s. The aim of this paper is to give a review on some of the most acknowledged methods of match analysis in table tennis. The first chapter presents a historical overview of match analysis from all over the world. The second part reviews different approaches to match analysis in more detail, using the performance analysis classification of theoretical and practical performance analysis. The review includes the most actual theoretical performance analysis techniques in table tennis: performance indices, simulative approaches, momentum analysis, footwork analysis, and finally an approach which uses top expert knowledge for a comprehensive technical-tactical analysis. In the section of practical performance analysis, the paper presents two "best practice" examples describing performance analysis procedures of the two most successful countries of the last Olympics: China and Japan. The paper ends with a summary on the impact of the different approaches and gives an outlook on promising new developments.